Premises for Adapting Curriculum and Educational Package to Labor Market Requirements - Mladen, Luise; Tonis (Bucea-Manea), Rocsana (Journal of Economic Development, Environment and People, 2016)
From all times it has been demonstrated that human resource is the most important and valuable asset for a company. Investing in human resource training and education should be a priority for organizations and universities. As the investments to bring benefits for economy the communication and collaboration between organizations (market) and universities (school) must be very close. As a consequence the scope of the paper was to identify the measures necessary to improve the existing university curriculum by linking with the labor market requirements. In this regard was implemented a market research within, “Adapt2jobs” POSDRU project, in 2 steps: a survey for organization and a survey for students. The article presents the results of the qualitative and quantitative results of the analysis regarding the market demand, the requirements of organizations for employees.